1980
DOI: 10.1007/bf01909459
|View full text |Cite
|
Sign up to set email alerts
|

Influence of molecular weight on the dynamic mechanical properties of poly(methyl methacrylate)

Abstract: Using a new parallel beam apparatus, the dynamic mechanical properties of poly-(methyl methacrylate) were determined over a wide range of molecular weights (1500 < < Mn < 600 000). Results showed that the modulus (25 ~ was only slightly dependent on chain length, and equalled 2.3 • 109 Pa for the highest molecular weight scanned. Simultaneous acquisition of ct-and fl-relaxations indicated a decrease in T, in accordance with Gibbs' relation, while T~ was invariant. Both T~ ~ = 111 ~ and T~ = 40 ~ corroborated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 20 publications
(20 reference statements)
2
3
0
Order By: Relevance
“…It has been shown that the molecular weight of PMMA influences the flexural modulus of cross-linked dentures based on this polymer [7]; increasing the molecular weight from 120,000 to 220,000 (corresponding to an increase in the number of monomers from about 1,200 and 2,200 respectively) significantly increases the modulus. The molecular weight of PMMA also influences the modulus at room temperature measured using the dynamic mechanical analysis technique (DMA) [40] and the modulus of elasticity measured using transverse deflection [41]. The current work also shows a similar trend of an increase in the Young's modulus with an increase of the number of monomer units (Table 2).…”
Section: Resultssupporting
confidence: 66%
“…It has been shown that the molecular weight of PMMA influences the flexural modulus of cross-linked dentures based on this polymer [7]; increasing the molecular weight from 120,000 to 220,000 (corresponding to an increase in the number of monomers from about 1,200 and 2,200 respectively) significantly increases the modulus. The molecular weight of PMMA also influences the modulus at room temperature measured using the dynamic mechanical analysis technique (DMA) [40] and the modulus of elasticity measured using transverse deflection [41]. The current work also shows a similar trend of an increase in the Young's modulus with an increase of the number of monomer units (Table 2).…”
Section: Resultssupporting
confidence: 66%
“…The viscoelastic behaviour of the thermal cure system Lucitone and the microwave cure system Acron MC appear to parallel the previously reported modulus changes of PMMA denture resin systems [, [10][11][12][13]. Loss modulus peak (obtained at low frequencies) is often considered as a better indicator of glass transition temperature (Zg) than tan delta peak because it closely corresponds to the Tg value determined by other methods such as DTA, whereas tan delta peak occurs at 5-15 °C higher [14].…”
Section: Discussion Of Resultssupporting
confidence: 55%
“…Because of the wide range of mechanical behaviour involved, and the close relationship of this mechanical behaviour with the viscoelastic properties centred around one or more glass transition phenomena (such as the a, [3 or other transitions), dynamic mechanical analysis (DMA) is a very valuable method to characterize dental polymeric systems. The sensitivity of DMA for the detection of glass transitions is well known and many investigators have used the technique to characterize viscoelastic properties of different dental polymers [1][2][3][4][5][6][7][8][9][10][11][12][13]. The information provided in DMA tests, such as storage modulus, loss modulus and tan delta, have been used to study heat cure denture resins in the past [10 13].…”
Section: Introductionmentioning
confidence: 99%
“…PMMA and its copolymers or composites are widely used in electronic equipment, medical technology, and polymer membranes areas. The relationship between molecular weight and physical properties is deeply investigated [77,78]. For instance, the mechanical properties of PMMA are significantly affected by the molecular weight (Figure 7).…”
Section: Applications Of High Molecular Weight Pmmamentioning
confidence: 99%